Petrie paths in triangular mormalizer maps - YAZICI GÖZÜTOK, NAZLI (My University, 2022)
This study is devoted to investigate the Petrie paths in the normalizer maps and regular triangular maps corresponding to the subgroups Γ0(N) of the modular group Γ. We show that each regular triangular map admits a closed Petrie path. Thus, for each regular map, we find the Petrie length of the corresponding map.
Keywords: Matematik; Kombinatorik; Temel Bilimler; Mathematics; Combinatorics; Natural Sciences; Temel Bilimler (SCI); Doğa Bilimleri Genel; ÇOK DİSİPLİNLİ BİLİMLER; MATEMATİK; Natural Sciences (SCI); NATURAL SCIENCES, GENERAL; MATHEMATICS; MULTIDISCIPLINARY SCIENCES; Mantık; Geometri ve Topoloji; Ayrık Matematik ve Kombinatorik; Multidisipliner; Fizik Bilimleri; Logic; Geometry and Topology; Discrete Mathematics and Combinatorics; Multidisciplinary; Physical Sciences; Normalizer; Petrie path; Regular map